Students’ and supervisors’ knowledge and attitudes regarding plagiarism and referencing - Lindahl, Johanna F.; Grace, Delia (Springer, 2018)
Background Referencing is an integral part of scientific writing and professional research conduct that requires appropriate acknowledgement of others’ work and avoidance of plagiarism. University students should understand and apply this as part of their academic development, but for this, it is essential that supervisors also display proper research integrity and support. Methods This study used an online educative questionnaire to understand the knowledge and attitudes of students and supervisors at two institutes in Europe and Africa. The results were then used to create discussion around education of students and faculty in workshops and lectures. Results Overall, 138 students and 14 supervisors participated: most were Swedish (89) and Kenyan (11). Overall, 98% had heard about plagiarism, and 35% believed it was common. Only 45% had heard about self-plagiarism, and when explained what it was, 44.5% considered it morally wrong. Europeans and North Americans had more knowledge than other nationalities. Most (85%) had received some training on referencing, but there was little consensus about principles, with more than 30% considering it acceptable to cite a reference in a paper they had not read. Discussing these results and the questions in workshops was helpful; it was also clear that there was no consensus among supervisors on what constituted correct behavior. Conclusions This survey shows a need for greater consensus on appropriate referencing, and that there is need for more discussions and training on the topic for both students and faculty.